Jews in the Japanese mind : the history and uses of a cultural stereotype - Goodman, David G. (Free Press, 1995)
The popularity in Japan of books about Jews has climbed to staggering proportions. Such books have sold millions of copies and often top the best-seller list. What explains the virtual obsession with Jews in Japan - a country that has no Jews? Many of the Japanese books about Jews are overtly antisemitic; but even a large number of otherwise respectable scholarly books are replete with egregious distortions and antisemitic canards, such as references to the Protocols of the Elders of Zion, a notorious antisemitic forgery, as though it were a serious work of social and historical analysis; and most propagate the myth that Jews control the American media and dominate international finance